The Effect of Supervision on The Effectiveness of The Public Health Program In Cimaung Village - Pandji Santosa (Universitas Sultan Ageng Tirtayasa, 2022)
This research is motivated by the ineffectiveness of the implementation of the Family Hope Program Case Study of Public Health in Cimaung Village, Cimaung District, Bandung Regency. Based on these problems, it can be formulated as follows